Indigenous-owned businesses in Canada, 2005 to 2021 - Bassirou Gueye (Economic and Social Reports)
As the economic landscape evolves, and with the effects of the COVID-19 pandemic reshaping business environments, it is essential to support evidence-based policymaking and to develop inclusive strategies that foster growth and resilience within the Indigenous business sector. Funded by Indigenous Services Canada, this study is an update to previous research that provides an overview of Indigenous-owned businesses in Canada.